Standardization of marketed formulation Kipen Tablet for analgesic and anti-inflammatory potential - Ansari, Md. Sarfuddin; Basedia, Deepak Kumar; Dubey, B. K. (Asian Journal of Pharmaceutical Research and Development, 2021)
The primary objective of the current investigation was to standardize the formulation Kipen Tablet marketed as patented and proprietary medicine for treatment of various conditions of Pitta, according to the WHO guidelines. The procured tablets of Kipen were Light green in color, with no odor and a bitter taste. Kipen exhibited 8.1% total ash with 2.35% acid insoluble ash and 4.95% water soluble ash. The water soluble and alcohol soluble extractives were 1.36% and 1.3% respectively. The results of preliminary qualitative phytochemical screening revealed that all the classes of phytochemicals were present in Kipen. TLC analysis of Kipen was done using Curcumin as the marker using ethyleacetate: n-hexane (3:7) as the solvent system. Curcumin appeared at Rf value of 0.56 on the TLC plate. The quantitation of the curcumin was done by HPLC method and it was found that Kipen contained 3.75 mg curcumin per 250 mg of Kipen (1.5 %). The anti-inflammatory activity was evaluated using carrageenan induced rat paw edema method and it was seen that Kipen was able to inhibit about 51% edema formation in rat paws. The analgesic action of Kipen was evaluated using tail flick method and the response time pain stimulus (thermal) was observed. The highest reaction time for Kipen was 6.26 ± 0.06.15 ± 0.242 sec at 30 min post administration while it was 3.46 ± 0.095 sec and 6.22 ± 0.171 sec for vehicle treated and Ibuprofen treated group respectively at the same time duration.